2019
DOI: 10.1016/j.reth.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

“Microgravity” as a unique and useful stem cell culture environment for cell-based therapy

Abstract: Cell-based therapy using mesenchymal stem cells or pluripotent stem cells such as induced pluripotent stem cells has seen dramatic progress in recent years. Part of cell-based therapy are already covered by public medical insurance. Recently, researchers have attempted to improve therapeutic effects toward various diseases by cell transplantation. Culture environment is considered to be one of the most important factors affecting therapeutic effects, in particular factors such as physical stimuli, because cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…Another important aspect of RCCS is the rotational speed. Previous studies have reported speeds ranging from 12 to 48 rpm/min, and no universal rotational speed has been identified [ [26] , [27] , [28] ]. Difference in rotational speed may lead to different mechanical stimulation, which can generate diverse cell states.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of RCCS is the rotational speed. Previous studies have reported speeds ranging from 12 to 48 rpm/min, and no universal rotational speed has been identified [ [26] , [27] , [28] ]. Difference in rotational speed may lead to different mechanical stimulation, which can generate diverse cell states.…”
Section: Discussionmentioning
confidence: 99%
“…hBMSCs are able to migrate into damaged tissues and perform wound healing through two key mechanisms, that is, paracrine and direct differentiation. Indeed, the migration of hBMSCs is regulated by mechanical and chemical factors in this trafficking process ( Imura et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed the changes of rostral-caudal neural patterning genes and cortical markers in human embryonic stem cell (hESC)-derived neural organoids cultured in microgravity conditions compared with standard conditions [36]. Additionally, emerging evidence indicates that microgravity affects not only cell differentiation but also the therapeutic effect of transplanted cells [15,37]. Several studies have demonstrated that microgravity contributes to providing seeding cells for cell therapy and enhancing the therapeutic effect of stem cell transplantation [38][39][40].…”
Section: Discussionmentioning
confidence: 99%